Study on the absenteeism of sewers at International Ying Ming Industrial Company - Cortes, Ma. Jonah S.
Absenteeism of sewers is considered as a serious problem of International Ying Ming Industrial Comapny (IYMIC). This study attempts to find solutions to this problem. Three major objectives were met. First, the determination of the trends of absenteeism during during near Sundays, near Holidays and Paydays. Second, evaluation of the distribution of absentees by age, gender, civil status, and job status. And, third, the investigation of the reasons for absenteeism. Data used were based on primary and secondary sources. The data were cross-tabulated and analyzed using descriptive statistics such as percentage distribution and frequency count. Further analyses of the association of age, gender, civil status, and job status with incidence of absenteeism, Phi Coefficient and Pearson's Product Moment Correlation were used. Data analyses showed that the sewers of IYMIC have the tendency of extending vacation. Thus paydays do not hinder the sewers to absent. It was also found that female sewers have the highest incidence of absenteeism, same with the single (56.30%) and permanent sewers (53.09%). Among the male sewers, which is of relatively smaller population (25) 100% of them were absent. There were almost 62% of the female population who were absent. All in all, there was a 63% absence rate mainly from the sewing assembly department. Of the age group, those within the 18-29 years age bracket had the highest rate of absenteeism (49.33%). Third objective revealed that in most classifications 50.10% of absences were because of family reasons such as attending and going to the province which is probably because of close family ties. Illness comes as second reason (35.87%) such as body pain and diarrhea maybe because of poor safety and sanitary measures. Miscellaneous category, which includes traffic and weather condition is the third most common reasons and the fourth and last is social reasons which consists of filing of insurance and going to the bank and other related activities.